Analysis Quality Of Bus Trans Binjai Services Towards Improving Public Services in Binjai City - Khaidir Ali; Rafieqah Nalar Rizky (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
Transportation is part of road traffic and plays a role in improving community welfare. In September 2017, the Minister of Transportation together with the Mayor of Binjai inaugurated the operation of the Trans Binjai Bus. The aim of this research is to examine how to improve the quality of Trans Binjai Bus operational services in an effort to improve public services in Binjai City. The quality of service included in this is helping improve service to the community so that the level of service can provide satisfaction for customers. This research uses qualitative methods with descriptive analysis to obtain a systematic, factual and accurate picture of the problems studied. The results of this research indicate that the quality of Trans Binjai Bus operational services has been carried out quite well and is carried out as optimally as possible. The quality of services provided is supported by facilities and information services that still use manual methods. So this encourages the Binjai City Transportation Department to strive to implement application-based service improvements in the future in order to improve service quality and public comfort.